The unique N-terminal sequence of the BK(Ca) channel α-subunit determines its modulation by β-subunits - Lorca, Ramón A. (PLoS One, 2017)
Large conductance voltage- and Ca(2+)-activated K(+) (BK(Ca)) channels are essential regulators of membrane excitability in a wide variety of cells and tissues. An important mechanism of modulation of BK(Ca) channel activity is its association with auxiliary subunits. In smooth muscle cells, the most predominant regulatory subunit of BK(Ca) channels is the β1-subunit. We have previously described that BK(Ca) channels with distinctive N-terminal ends (starting with the amino acid sequence MDAL, MSSN or MANG) are differentially modulated by the β1-subunit, but not by the β2. Here we extended our studies to understand how the distinct N-terminal regions differentially modulate channel activity by β-subunits. We recorded inside-out single-channel currents from HEK293T cells co-expressing the BK(Ca) containing three N-terminal sequences with two β1-β2 chimeric constructs containing the extracellular loop of β1 or β2, and the transmembrane and cytoplasmic domains of β2 or β1, respectively. Both β chimeric constructs induced leftward shifts of voltage-activation curves of channels starting with MANG and MDAL, in the presence of 10 or 100 μM intracellular Ca(2+). However, MSSN showed no shift of the voltage-activation, at the same Ca(2+) concentrations. The presence of the extracellular loop of β1 in the chimera resembled results seen with the full β1 subunit, suggesting that the extracellular region of β1 might be responsible for the lack of modulation observed in MSSN. We further studied a poly-serine stretch present in the N-terminal region of MSSN and observed that the voltage-activation curves of BK(Ca) channels either containing or lacking this poly-serine stretch were leftward shifted by β1-subunit in a similar way. Overall, our results provide further insights into the mechanism of modulation of the different N-terminal regions of the BK(Ca) channel by β-subunits and highlight the extension of this region of the channel as a form of modulation of channel activity.